(untitled) (World Science, 2016)
The article presents the modern technology of extruded feed. Given the main indicators of quality of the extrudate. Based on the above analysis, it developed a classification that allows to identify the most promising direction in the development and creation of the press - extruder for the preparation of animal feed with soy protein. Thus, the analysis showed that the most efficient implementation of the process of preparation of mixed fodders by extruding a mixture of cereal and soy components with an insoluble residue, as a result of the extrusion is a qualitative mixing of feed and barothermal processing.